(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Millimeter-wave (mmW) range for 5 G application becomes an attractive area of research. This allows communication at high speed and low latency rates. To meet this requirement, we require an antenna that can resonate at a particular frequency or covers multiband and ultraband. All these requirements are fulfilled by the patch antenna, which is small in size, less in weight, has good bandwidth, with less complexity. In this paper, we design an ultra-band antenna with C shape slot on its patch and one small slot on its ground plane. The resultant band covers frequencies from 25.99 GHz to 40 GHz with a maximum return loss of -20 dB. The presented antenna finds application in 5G mobile communication.